Costs of opioid overdose education and naloxone distribution in New York City. Issue 1 (1st December 2022) - Behrends, Czarina N.; Gutkind, Sarah; Winkelstein, Emily; Wright, Monique; Dolatshahi, Jennifer; Welch, Alice; Paone, Denise; Kunins, Hillary V.; Schackman, Bruce R.
Abstract: Background: Naloxone is an opioid antagonist medication that can be administered by lay people or medical professionals to reverse opioid overdoses and reduce overdose mortality. Cost was identified as a potential barrier to providing expanded overdose education and naloxone distribution (OEND) in New York City (NYC) in 2017. We estimated the cost of delivering OEND for different types of opioid overdose prevention programs (OOPPs) in NYC. Methods : We interviewed naloxone coordinators at 11 syringe service programs (SSPs) and 10 purposively sampled non-SSPs in NYC from December 2017 to September 2019. The samples included diverse non-SSP program types, program sizes, and OEND funding sources. We calculated one-time start up costs and ongoing operating costs using micro-costing methods to estimate the cost of personnel time and materials for OEND activities from the program perspective, but excluding naloxone kit costs. Results : Implementing an OEND program required a one-time median startup cost of $874 for SSPs and $2, 548 for other programs excluding overhead, with 80% of those costs attributed to time and travel for training staff. SSPs spent a median of $90 per staff member trained and non-SSPs spent $150 per staff member. The median monthly cost of OEND program activities excluding overhead was $1, 579 for SSPs and $2, 529 for non-SSPs. The costs for non-SSPs varied by size, with larger, multi-site programs having higher median costs compared to single-site programs. The estimated median cost per kit dispensed excluding and including overhead was $19 versus $25 per kit for SSPs, and $36 versus $43 per kit for non-SSPs, respectively. Conclusions : OEND operating costs vary by program type and number of sites. Funders should consider that providing free naloxone to OEND programs does not cover full operating costs. Further exploration of cost-effectiveness and program efficiency should be considered across different types of OEND settings.